Jordan Higher Bi- Homomorphism and Co- Jordan Higher Bi- Homomorphism on Banach Algebra (Baghdad Science Journal, 2021)
The concepts of higher Bi- homomorphism and Jordan higher Bi- homomorphism have been introduced and studied the relation between Jordan and ordinary higher Bi- homomorphism also the concepts of Co- higher Bi- homomorphism and  Co- Jordan higher Bi- homomorphism introduced  and the relation between them in Banach algebra have also been studied.